2016
DOI: 10.1016/j.bbrep.2015.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Exploring potential anticoagulant drug formulations using thrombin generation test

Abstract: SummaryMany anticoagulant drugs inhibiting proteins of the coagulation cascade have been developed. The main targets of anticoagulant drugs are thrombin and factor Xa; inhibiting these factors delays thrombus growth, thus preventing thrombosis while increasing bleeding risk. A balance between thrombosis and bleeding is ensured in the ‘therapeutic window’ of the anticoagulant drug concentration range. Novel anticoagulant drugs and combinations thereof are being developed. We rank coagulation factors as potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
(37 reference statements)
2
8
0
Order By: Relevance
“…Regarding U. lactuca food safety, elucidation of molecular mechanisms behind the biological effects on the coagulation in vitro (Pomin, 2012;Mourão, 2015) is still needed as a critical step to antithrombotic drug formulation (Zavyalova & Kopylov, 2016).…”
Section: Electrophoretic Analyses Reveal Physical-chemical Homogeneitmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding U. lactuca food safety, elucidation of molecular mechanisms behind the biological effects on the coagulation in vitro (Pomin, 2012;Mourão, 2015) is still needed as a critical step to antithrombotic drug formulation (Zavyalova & Kopylov, 2016).…”
Section: Electrophoretic Analyses Reveal Physical-chemical Homogeneitmentioning
confidence: 99%
“…Its anticoagulant mechanism is proved by antithrombin (AT)-binding specific pentasaccharide sequence, which it is not found in other natural sources (Pomin, 2012;Mourão, 2015). The main targets of the algal anticoagulants are the thrombin (Rodrigues et al, 2013;Mourão, 2015), the final enzyme that converts fibrinogen into fibrin clot (Castoldi & Rosing, 2011), and the factor Xa (Athukorala et al, 2006;Glauser et al, 2009;Mourão, 2015), a coagulation protease that generates thrombin (Zavyalova & Kopylov, 2016), and/or by independent effect of serpins (Quinderé et al, 2014), preventing thrombosis without producing hemorrhage (Rodrigues et al, 2011;Quinderé et al, 2014;Mourão, 2015). However, at high dose, SPs from seaweeds may lead to thrombosis due to activation of factor XII in the intrinsic coagulation system (Rodrigues et al, 2011;Quinderé et al, 2014;Mourão, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observation suggested that our system could also constitute as an useful tool to guide complementary analyses for antivirally active algal SPs development (Cardozo et al, 2007) in parallel to prevention of thrombosis in vitro (Nishiro et al, 1999;Mourão et al, 2001;Rodrigues et al 2016Rodrigues et al , 2017b as support to predict the risk of bleeding or coagulopathy (Castoldi & Rosing, 2011;Zavyalova & Kopylov, 2016) on the focus of patients subjected to antiviral treatment (Ghosh et al, 2004;Ghosh et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Biological Sciences Maringá, v. 39, n. 3, p. 283-292, July-Sept., 2017 time (PT), respectively, although emphasizing that these two in vitro tests do not reflect the hemostasis (Ferreira, Sousa, Dusse, & Carvalho, 2010). Given these limitations and the complexity of the coagulation process, thrombin generation (TG)-based assays would offer a better understanding of the in vivo event to measure TG in a blood plasma sample (Castoldi & Rosing, 2011;Xin, Chang, & Ovanesov, 2016) and analyze anticoagulants Zavyalova & Kopylov, 2016). Circulatory dysfunctions are usually associated with the sedentary lifestyle, poor eating habits and stress that potentially lead to venous thromboembolism, heart attack and pulmonary embolism as the most prevalent cardiovascular diseases worldwide, leading causing to patient death or else partial or total disability.…”
Section: Introductionmentioning
confidence: 99%